2017
DOI: 10.1007/s12072-017-9796-z
|View full text |Cite
|
Sign up to set email alerts
|

A simple bedside blood test (Fibrofast; FIB-5) is superior to FIB-4 index for the differentiation between non-significant and significant fibrosis in patients with chronic hepatitis C

Abstract: FIB-5 score at the new cutoff is superior to FIB-4 index for the differentiation between non-significant and significant fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
3
14
2
Order By: Relevance
“…PPV was in the range of 24%–80% as against 50% in the current study. Similarly, NPV was in the range of 75.3%–98% compared with 90.24% in this study 17 20–25 29. As compared with previous studies, FIB-4 was not helpful for the prediction of SF in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…PPV was in the range of 24%–80% as against 50% in the current study. Similarly, NPV was in the range of 75.3%–98% compared with 90.24% in this study 17 20–25 29. As compared with previous studies, FIB-4 was not helpful for the prediction of SF in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…PPV was 85.7% and 99% as against 18.75% (at cut-off ≥7.505) and 37.5% (at cut-off <0) in the current study. Similarly, NPV was 38.7% and 92% compared with 89.47% (at cut-off <0) and 90% (at cut-off ≥7.505) in this study 16 17. In our study, FIB-5 did not perform better as compared with previous studies.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Hepatitis C is the most public health stress in Egypt where HCV prevalence is the highest in the world. Egypt Health Issues Survey (2015) showed that between 15 and 59 years of age, about 10% of Egyptians had been infected with HCV infection, while 7% of them have chronic active hepatitis C [2].…”
Section: Introductionmentioning
confidence: 99%